(untitled) (Communications in Mathematical Research, 2020)
In this paper, we introduce several new subclasses of the function class Σ of bi-univalent functions analytic in the open unit disc defined by convolution. Furthermore, we investigate the bounds of the coefficients |a_2| and |a_3| for functions in these new subclasses. The results presented in this paper improve or generalize the recent works of other authors.